Reports of recovered memories of childhood abuse in therapy in France. Issue 9 (21st October 2019) - Dodier, Olivier; Patihis, Lawrence; Payoux, Mélany
ABSTRACT: Recovered memories of abuse in therapy are especially controversial if the clients were not aware they were abused before therapy. In the past, such memory recovery has led to legal action, as well as a debate about whether such memories might be repressed, forgotten, or false memories. More than two decades after the height of the controversy, it is unclear to what degree such memories are still recovered today, and to what extent it occurs in France. In our French survey of 1312 participants ( M age = 33; 53% female), 551 reported having done therapy at some point. Of that 551, 33 (6%) indicated they had recovered memories of abuse in therapy that they did not know about before therapy. Sexual abuse was the most commonly reported type that was recovered in therapy (79%). As in past research, discussing the possibility of repressed memories with therapists was associated with reports of recovered memories of abuse. Surprisingly, memory recovery occurred just as much in behavioural and cognitive therapies as it did in therapies focused on trauma. We found recovered memories in a proportion of clients who began therapy recently. Recovered memories in therapy appears to be an ongoing concern in France.